FACEBOOK: REVOLUSI KOMUNIKASI PEMASARAN ONLINE IBU-IBU UNTUK MENINGKATKAN PENDAPATAN KELUARGA - Suprajang, Sandi Eka; Murdinar, Hardining Estu; Latifah, Nunuk (Politeknik Ubaya, 2024)
This research examines how the social media platform Facebook has revolutionised online marketing communications, particularly for stay-at-home mothers. Facebook offers various features such as Facebook Page, Facebook Group, and Facebook Marketplace that help mums start and grow businesses from home. Through qualitative methods with in-depth interviews and case studies, this research explores the impact of using Facebook on increasing family income. The findings show that Facebook Page helps in building brand awareness, Facebook Group provides a community of support and collaboration opportunities, while Facebook Marketplace facilitates easy and fast buying and selling transactions. Although there are challenges such as fierce competition and maintaining service quality, mothers can overcome them with the right strategies. In conclusion, Facebook plays an important role in the economic empowerment of housewives, enabling them to contribute to the family income significantly. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License.